PERBANDINGAN ANTARA â€œBIGâ€ WEB SERVICE DENGAN RESTFUL WEB SERVICE UNTUK INTEGRASI DATA BERFORMAT GML - Nugroho, Adi; Mustofa, Khabib (Institute of Research and Community Outreach - Petra Christian University, 2012)
Web Service with Java: SOAP (JAX-WS/Java API for XML Web Services) and Java RESTful Web Service (JAX-RS/Java RESTful API for XML Web Services) are now a technology competing with each other in terms of their use for integrates data residing in different systems. Both Web Service technologies, of course, have advantages and disadvantages. In this paper, we discuss the comparison of the two technologies is a Java Web Service in relation to the development of GIS application (Geographic Information System) integrates the use of data-formatted GML (Geography Markup Language), which is stored in the system database XML (eXtensible Markup Language).